Neural nonpartisans. Issue 3 (3rd July 2022) - Schreiber, Darren; Fonzo, Greg; Simmons, Alan; Dawes, Chris; Flagan, Taru; Paulus, Martin
ABSTRACT: While affective conflict between partisans is driving much of modern politics, it is also driving increasing numbers to eschew partisan labels. A dominant theory is that these self-proclaimed independents are merely covert partisans. In the largest functional brain imaging study of neuropolitics to date, we find differences between partisans and nonpartisans in the right medial temporal pole, orbitofrontal/medial prefrontal cortex, and right ventrolateral prefrontal cortex, three regions often engaged during social cognition. These results suggest that rather than being simply covert partisans, nonpartisans process the world in a way different from their partisan counterparts.